Politainment and Celebrity Officials in Online Journalism: A Study of Kompas.com and Public Discourse in Indonesia - Cahyani, Dewi Y (JURNAL KOMUNIKASI INDONESIA, 2026)
This study examines how politainment shapes the news coverage of public officials with celebrity backgrounds (celebrity officials) in Indonesia's post-electoral governance context. Focusing on Kompas.com during the first six months of the Prabowo–Gibran administration, the study integrates theories and concepts of politainment, celebrity politics, and the public sphere to address a gap in global scholarship. Existing research has largely focused on Western democracies, electoral campaigns, and social media platforms, while paying limited attention to how politainment operates within professional online journalism in emerging democracies. Using a mixed-method approach that combines quantitative content analysis of 102 news articles with qualitative framing analysis, the findings show that Kompas.compredominantly frames celebrity officials through personalization, symbolic visibility, and affective narratives, with limited emphasis on policy substance or administrative performance. These results suggest that politainment has become institutionalized in routine political reporting not merely as a campaign strategy, but as a dominant mode of post-election public communication. This study contributes to the studies on the mediatization of politics by demonstrating how politainment in post-reform Indonesia constrains rational public discourse and poses challenges to journalistic responsibility and democratic deliberation.